THIN LAYER CHROMATOGRAPHY ANALYSIS OF SIMHANAD GUGGULU PILL - Saroj Kumar Debnath; Sudhaben N. Vyas (International Journal of Applied Ayurved Research, 2015)
It is being internationally accepted that medicinal plants play an important role for providing health benefits. Maximum Ayurvedic medicines are plant based drugs. It is a major challenge for quality control of plant based Ayurvedic drugs due to its complex composition. Thin layer chromatography is an important parameter for standardization of the plant based Ayurvedic drugs. One most important Ayurvedic drug i.e. Simhanad Guggulu pill had been selected from famous Ayurvedic book named Bhaishajya Ratnavali for Thin layer chromatography analysis. It is mainly and commonly used in the treatment of disease Amavata (Rheumatoid arthritis). Medicine preparing and Thin layer chromatography analysis both had been done in the Institute for Post Graduate Teaching and Research in Ayurveda, Gujarat Ayurved University, Jamnagar. Seven phytocostitutents were indicated under short ultra violet ray (254 nm) and eight phytocostitutents were indicated under long ultra violet ray (366 nm) by the Thin layer chromatography analysis on the sample of Simhanad Guggulu pill.